The impact on physical performance, pain and psychological wellbeing of chronic low back pain patients during 12-weeks of equine- facilitated therapy intervention - Mattila-Rautiainen, Sanna; Venojärvi, Mika; Rautiainen, Heta; Keski-Valkama, Alice (Frontiers in Veterinary Science, 2023)
Equine - Facilitated Therapy (EFT), an equine environment, and horses themselves can meet many physical and mental health needs beyond diagnostic categories. The horse's ability to produce a walk-like movement and the participant's ability to connect to non-judgemental living creatures, both of which can benefit participation and construct a positive self-image for chronic pain patients. The objective of this study is to evaluate the impact of EFT on perceived physical performance, level of pain, pain acceptance, depression and anxiety, and quality of life within a 12-week intervention for chronic low back pain (LBP) patients. Twenty-two LBP patients received EFT led by physical therapists as part of the public health services. A mixed method design combining quantitative and qualitative methods was employed to detect the outcome of the intervention. The data were collected via questionnaires, interviews, and patient data repositories. An interview was voluntary for participants and included questions of one's health, visits to the pain clinic during 6 months and an open-ended question about the intervention. The coding of the data was completed independently by two persons using thematizing. The welfare of the attending horses was taken into consideration in basic training and for the research setting. Statistical analysis and paired t-tests detected the changes during a 12-week intervention. The results suggest a significant increase in Canadian Occupational Performance Measure (COPM) levels of satisfaction with self-selected performances. The Raitasalo's version of Beck's Depression Inventory (RBDI) level of anxiety and Chronic Pain Acceptance Questionnaire (CPAQ) did not change, whereas a decline in the amount of perceived RBDI depression was found combined with increased levels of SF-36 Mental Change Scores and COPM satisfaction with performance. Only two of the 22 participants returned with reoccurring symptoms after 6 months to the pain clinic. The participant interviews revealed three important domains of experience during coding: physical-, psychological-, and social that link to the research question and suggest impact for the recovery from the human-animal interaction.